Sedative and Analgesic Drugs Online: A Content Analysis of the Supply and Demand Information Available in Thailand - Kanokporn Pinyopornpanish (2018)
© 2018 Taylor & Francis Group, LLC. Background: Evidence from other countries has suggested that many controlled drugs are also offered online, even though it is illegal to sell these drugs without a license. Objectives: To evaluate the current contents related to the supply and demand of sedatives and analgesic drugs available online in Thailand, with a particular focus on Facebook. Methods: A team of reviewers manually searched for data by entering keywords related to analgesic drugs and sedatives. The contents of the website were screened for supply and demand-related information. Findings: A total of 5,352 websites were found publicly available. The number of websites and Facebook pages containing the information potentially related to the supply and demand of analgesic drugs and sedatives was limited. Nine websites sold sedatives, and six websites sold analgesics directly. Fourteen Facebook pages were found, including 7 sedative pages and 7 analgesic pages. Within one year, the three remaining active pages multiplied in the number of followers by three- to nine-fold. The most popular Facebook page had over 2,900 followers. Conclusions: Both the internet and social media contain sites and pages where sedatives and analgesics are illegally advertised. These websites are searchable through common search engines. Although the number of websites is limited, the number of followers on these Facebook pages does suggest a growing number of people who are interested in such pages. Our study emphasized the importance of monitoring and developing potential plans relative to the online marketing of prescription drugs in Thailand.